Carmen Dagostino, Marianne Mithun, and Karen Rice (eds.) 2023 (vol. 1), 2024 (vol. 2). The languages and linguistics of indigenous North America: A comprehensive guide, Volume 1; Volume 2. (The World of Linguistics 13.1-2). Berlin – Boston: De Gruyter Mouton . Pp. LII (front matter) + 1-715 + separate enlarged map insert (vol. 1), and + pp. XII (front matter) + [987] 717-1702 (vol. 2) - Majewicz, Alfred F. (Lingua Posnaniensis, 2026)
Review: Carmen Dagostino, Marianne Mithun, and Karen Rice (eds.) 2023 (vol. 1), 2024 (vol. 2). The languages and linguistics of indigenous North America: A comprehensive guide, Volume 1; Volume 2. (The World of Linguistics 13.1-2). Berlin – Boston: De Gruyter Mouton . Pp. LII (front matter) + 1-715 + separate enlarged map insert (vol. 1), and + pp. XII (front matter) + [987] 717-1702 (vol. 2)